California Vital Statistics and Homicide Data, 1990-1999 - Van Court, Jason ([Verlag nicht ermittelbar], 2002)
This data collection resulted from the project "Linked Homicide File for 1990-1999," which was conducted by the California Department of Health Services (CDHS), Epidemiology and Prevention for Injury Control Branch, for the purpose of studying homicide and providing evidence for the development of strategies to reduce homicide in California. The researchers combined the strengths of law enforcement reporting and medical reporting in one dataset. The homicide data contain information on victims and circumstances of the 34,542 homicides investigated by law enforcement agencies in California for the period 1990 to 1999. The data are Supplementary Homicide Reports (SHR), which are received monthly by the Department of Justice from all local California law enforcement agencies as part of the national Uniform Crime Reporting program (UNIFORM CRIME REPORTS [UNITED STATES]: SUPPLEMENTARY HOMICIDE REPORTS, 1976-1999 [ICPSR 3180]). The researchers linked the SHRs to the CDHS vital statistics mortality data, which contain the death records provided by the medical examiner or coroner of each county after investigation of the death. Variables include total number of offenders involved, weapon used in the homicide, county of the victim's residence, location and date of the incident, date of death, cause of death, date of arrest for the suspect, and whether supplemental homicide report matched the death record. Demographic data include age, sex, and race of the victim and the suspect, relationships between the suspect and the victim, and the victim's marital status.